2000
DOI: 10.1099/00221287-146-3-599
|View full text |Cite
|
Sign up to set email alerts
|

A bacteriophage-like particle from Bartonella bacilliformis

Abstract: Bartonella bacilliformis and Bartonella henselae, the respective agents of Oroya fever and cat-scratch disease in humans, are known to produce bacteriophage-like particles (BLPs) that package 14 kbp segments of the host chromosome. Data from this study suggest that other Bartonella species including Bartonella quintana, Bartonella doshiae and Bartonella grahamii also contain similar BLPs, as evidenced by the presence of a 14 kbp extrachromosomal DNA element in their genomes, whereas Bartonella elizabethae and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 33 publications
4
28
0
Order By: Relevance
“…Phage particles with multiple head sizes were detected, although it was not clear if the variation in particle size was an artifact of the isolation protocol, as ultracentrifugation can alter the appearance of phage particles. Consistent with the observations of Anderson and Barbian (1,3), no phage tails were evident in the phage preparations.…”
Section: Resultssupporting
confidence: 79%
“…Phage particles with multiple head sizes were detected, although it was not clear if the variation in particle size was an artifact of the isolation protocol, as ultracentrifugation can alter the appearance of phage particles. Consistent with the observations of Anderson and Barbian (1,3), no phage tails were evident in the phage preparations.…”
Section: Resultssupporting
confidence: 79%
“…In order to estimate the molecular weights of the proteins in the samples, the migration of each band was compared to the migration of the protein standards of known molecular weights in the molecular ladder. SDS PAGE analysis of purified bacteriophages showed three major bands, with molecular masses of 47, 34 and 16 kDa Figure (4), this range nearly agreed (Barbian and Minnick, 2000) who found that SDS-PAGE analysis of purified bacteriophage-like particle from Bartonella Bacilliformis showed three major proteins with apparent molecular masses of 32, 34 and 36 kDa; values that closely correspond to proteins found in B. henselae BLPs. The results also agreed (Zimmer, et al, 2002) who found the major capsid component results in size from 47.7 to 34.3 KDa resembles 43.3% of total phage protein and the tail protein corresponds to 12.7% with an apparent size of 27 kDa.…”
Section: Fig 3: Ratio Of Dry Weight Samplessupporting
confidence: 66%
“…The B. henselae particles contain seemingly random 14 kb pieces of the host genome, on the basis of the gel banding pattern after restriction endonuclease digestion, sequence analysis of cloned DNA from the particles and Southern blot hybridization 117 . Analysis of the DNA from the B. bacilliformis BLPs indicated that the genomic origin of the packaged DNA is biased to certain regions 118 . A more recent study used whole-genome microarrays to characterize DNA packaging by BLPs produced by Bartonella grahamii 115 .…”
Section: Boxmentioning
confidence: 99%